Effects of Metacognitive Scaffolding Embedded in Cooperative Setting on Mathematical Reasoning and Metacognitive Knowledge - Jbeili , Ibrahim (Jordan Journal of Educational Sciences, 2013)
metacognitive scaffolding embedded in cooperative setting method (Method1) and cooperative learning alone method (Method2) on fifth-graders’ mathematical reasoning and metacognitive knowledge. 240 fifth grade male students were randomly selected from three different schools to participate in this study. Students were divided into three groups: Students in the first group were taught via Method 1, students in the second group were taught via Method2, and students in the third group were taught via Method 3 as a control group. To achieve the aim of the study, Method1 was compared to Method2 and to Method3 using a quasi-experimental design, also Method2 compared to Method3. A mathematical reasoning test and a metacognitive knowledge questionnaire were administered following the implementation of the instructional methods on the unit of “Adding and Subtracting Fractions”. Data analyses were carried out using Multivariate Analysis of Covariance (MANCOVA).The results showed that students taught via Method1significantly outperformed students taught via Method2 and Method3 in mathematical reasoning and metacognitive knowledge. The results also showed that students taught via Method2 significantly outperformed students taught via Method3 in mathematical reasoning and metacognitive knowledge.